Let-7-mediated suppression of mucin 1 expression in the mouse uterus during embryo implantation - INYAWILERT, Wilasinee (J Reprod Dev, 2015)
Mucin 1 (Muc1) is an integral transmembrane mucin glycoprotein expressed on the apical surface of most epithelia. It is considered to be a barrier to the regulation of embryo implantation by inhibiting attachment of the embryo to the endometrium. Therefore, loss of Muc1 on the surface of uterine epithelial cells is necessary for embryo implantation. Studies have demonstrated that microRNAs (miRNAs) play a key role in enhancing embryo implantation in mammals. In this study, we investigated the regulatory role of two miRNAs (let-7a and let-7b) on the expression of Muc1 in mouse uteri during implantation. Western blotting indicated that Muc1 expression was highest on day1 of pregnancy and constantly decreased thereafter until day 4. In contrast to Muc1 expression, increased expression of let-7a and let-7b was evident on day 4 of pregnancy as measured by real-time reverse transcription-polymerase chain reaction (real-time RT-PCR). We demonstrated direct binding of let-7a and let-7b to the 3’untranslated region of muc1. Furthermore, Muc1 expression was suppressed after transfection of mouse uterine epithelial cells isolated from day 1 of pregnancy with let-7a and let-7b. In summary, the present study provides evidence that Muc1 is a direct target of let-7a and let-7b. Additionally, the current study suggests that miRNAs are novel targets which can be used to facilitate a successful pregnancy and repair implantation failure.